The current practice of assisted hatching for embryos in fertility centres: a general survey - Liu, Y; Jones, C; Coward, K (Springer, 2022)
At present, there is no standardised protocol for assisted hatching (AH) and the field is beset with contradictory data. We hypothesised that such contradiction may be related to inconsistencies in clinical practice. This study aimed to investigate the application, preferences, and variations of AH in current clinical practice prior to embryo transfer (AHpET) and biopsy (AHpBP). An online voluntary survey, consisted of 25 questions regarding different aspects of AH, was circulated amongst different fertility centres via newsletters between October 2019 and March 2020. One-hundred twenty-nine different fertility centres participated in the survey. AHpBP was widely used (90.6% [48/53]) amongst these centres, especially for trophectoderm biopsy (92.2% [47/51]). In contrast, only 64.6% (73/113) of centres administrated AHpET; the application of AHpET was even lower in UK-based centres (36.6% [15/41]). Although laser pulses have become the predominant technique for AH, significant variation existed in the precise strategy. Zona pellucida (ZP) drilling was the main method for AHpBP, whilst both ZP drilling and ZP thinning were applied equally for AHpET. Furthermore, the ZP manipulation varied widely with regards to the size of the ZP opening and the extension of ZP thinning. This is the first representative survey relating to the current practice of AH. Laser-assisted AH is used extensively, especially for AHpBP. However, there is significant disparity in clinical practice across different centres. Future research should aim to create a standardised protocol for AH to help reduce the evident variation in clinical practice and investigate the true value of AH.